Confirming Maximal Oxygen Uptake: Is Heart Rate the Answer? - Keiller, Don; Gordon, Dan (International Journal of Sports Medicine, 2018)
This study investigates heart rate (HR), in 11 young adults (22.4±3.21yr), at V̇O2max, to ascertain whether measured maximal heart rate (HRmax), as determined by a plateau in HR (HRplat), can reliably confirm V̇O2max. V̇O2max and HRplat were determined, using the parameters of a V̇O2≤50 ml•min−1 and a ∆HR≤2b•min−1, respectively, over the final 60 s of sampling. V̇O2 was also independently determined using a verification phase protocol. A HRplat was achieved by 91% of participants (∆HR=1.3±1b•min−1) and critically the time at which HRmax was reached coincided with that at which V̇O2max was achieved. Moreover RER and ΔRER criteria were reached significantly earlier (p<0.05) than V̇O2max, whilst age-related heart rate maximums (HRage), were not achieved by many participants. The results suggest that a HRplat ≤2 b•min−1 is a more accurate method, within the group tested, to determine whether a ‘true’ V̇O2max has been achieved, than other secondary criteria and potentially avoids the requirement for an additional verification phase.
Keywords: plateau; criteria; verification; cardiac response; VO 2max